Super (a,d)-edge-antimagic total labeling of connected Disc Brake graph - Arianti, Inge Yosanda; Dafik, Dafik; Slamin, Slamin (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
Super edge-antimagic total labeling of a graph G=(V,E) with order p and size q, is a vertex labeling {1,2,3,...p} and an edge labeling {p+1,p+2,...p+q} such that the edge-weights, w(uv)=f(u)+f(v)+f(uv), uv E(G) form an arithmetic sequence and for a>0 and d≥ 0, where f(u) is a label of vertex u, f(v) is a label of vertex v and f(uv) is a label of edge uv. In this paper we discuss about super edge-antimagic total labelings properties of connective Disc Brake graph, denoted by Db_n,p. The result shows that a connected Disc Brake graph admit a super (a,d)-edge antimagic total labeling for d=0,1,2, n≥ 3, n is odd and p≥ 2. It can be concluded that the result has covered all the feasible d.